Impact of varied nitrogen levels on agronomic performance and efficiency of nitrogen utilization by different wheat cultivars under salt-affected soil conditions - Noura H.A. AWAAD; Ayman M. HELMY; Sara E. FOUDA; Rehab H. HEGAB; Khadiga ALHARBI; Ahmed S. ELRYS; Elsayed MANSOUR; Hassan A. AWAAD (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
Optimizing nitrogen fertilization is vital for enhancing wheat productivity and ensuring sustainable agriculture in salt-affected soils. This study aimed to identify optimal nitrogen level for improving agronomic performance of diverse wheat cultivars (Sakha 95, Giza 171, and Misr 3) in salt-affected soil (9.18 dS/m). Four nitrogen levels (0, 96, 192, and 288 kg N per ha) were assessed. The results revealed significant differences among nitrogen levels and assessed cultivars in chlorophyll content, days to heading, flag leaf area, yield and its components, nutrient content (N, P, K), protein content, N uptake, nitrogen utilization efficiency (NUtE) and nitrogen use efficiency (NUE). Most traits improved with increasing nitrogen levels up to 288 kg N/ha, except for canopy temperature depression (CTD) and NUE, which decreased. Sakha 95 surpassed the other cultivars in several traits, including earliness, number of spikes, plant height, number of grains per spike, grain yield, straw yield, biological yield, nutrient content (N, P, K), grain N-uptake and total N-uptake. It also demonstrated the highest efficiencies in agronomic efficiency (AE), physiological efficiency (PE), apparent recovery efficiency (ARE), NUtE, and NUE. Otherwise, Misr 3 exhibited superior agro-physiological efficiency (APE). The interaction effects showed that Sakha 95 had the best earliness at 0 and 96 kg N/ha. Misr 3 achieved the highest grain phosphorus (P) content and PE at 288 kg N/ha. Giza 171 showed the highest chlorophyll content, CTD, flag leaf area, and several nutrient contents at 288 kg N/ha. The highest grain yield, biological yield, and nutrient uptake at 288 kg N/ha were recorded for Sakha 95. The tallest plants, with the uppermost number of grains per spike, AE, ARE, and NUtE, were found at 192 kg N/ha for Sakha 95. The uppermost NUtE and NUE at N0 were also noted for Sakha 95. Based on nitrogen sensitivity measurements, Misr 3 was the most tolerant to nitrogen deficiency stress, followed by Giza 171. These findings highlighted the importance of cultivar selection and nitrogen management in optimizing wheat production in salt-affected soils.